Algorithmic Rationality vs. Human Bias : A Comparative Review of Robo-Advisors in Portfolio Management - Kytölä, Veikko; Valtanen, Juuso (My University, 2026)
This thesis addresses a major conflict in modern finance. It is the gap between the ideas of Modern Portfolio Theory and the real-world investor decision-making. Cognitive biases are often shown by investors and therefore traditional human advisors were compared with algorithmic models. These models range from basic robo-advisors to advanced Agentic AI systems. The goal was to examine which option performs better and reduces investor biases more effectively. The results of the algorithm models show a clear advantage. They are used as commitment devices and to remove biases such as the Disposition Effect and overconfidence. This advantage is deepened by the emergence of Generative AI and Large Language Models. Algorithms can use these technologies to interpret market news free from emotional bias. They also predict returns more accurately than humans. Agentic AI introduces autonomous cost-efficiency by automating complex financial workflows without human participation. Relying only on technology is not enough. Algorithms bring in new risks, such as the "black box" problem and probable biases in the training data. Therefore, human advisors are still needed. They provide complete financial planning, explain complex model results, and offer psychological support. As a result, the thesis suggests a solution. A Hybrid Model, which combines the efficiency of AI with human decision-making and empathy, is the best approach for future portfolio management.

Tämä tutkielma käsittelee modernin rahoituksen suurta ristiriitaa. Kyseessä on kuilu modernin portfolioteorian ajatusten ja sijoittajien todellisen päätöksenteon välillä. Sijoittajilla esiintyy usein kognitiivisia vinoumia, ja siksi perinteisiä inhimillisiä neuvonantajia verrattiin algoritmisiin malleihin. Nämä mallit ulottuvat yksinkertaisista roboneuvojista edistyneisiin agenttisiin tekoälyjärjestelmiin. Tavoitteena oli tutkia, kumpi vaihtoehto suoriutuu paremmin ja vähentää sijoittajien vinoumia tehokkaammin. Algoritmisten mallien tulokset osoittavat selkeää etua. Niitä käytetään sitouttamisvälineinä poistamaan vinoumia, kuten disposition-ilmiötä ja yliluottamusta. Tätä etua syventävät entisestään generatiivinen tekoäly ja suuret kielimallit. Algoritmit voivat käyttää näitä teknologioita markkinauutisten tulkitsemiseen ilman emotionaalisia vinoumia. Ne myös ennustavat tuottoja ihmistä tarkemmin. Agenttinen tekoäly tuo mukanaan itseohjautuvaa kustannustehokkuutta automatisoimalla monimutkaisia rahoitusalan työnkulkuja ilman ihmisen osallistumista. Pelkkä teknologiaan tukeutuminen ei kuitenkaan riitä. Algoritmit tuovat mukanaan uusia riskejä, kuten "mustan laatikon" ongelman ja mahdolliset vinoumat opetusdatassa. Siksi inhimillisiä neuvonantajia tarvitaan edelleen. He tarjoavat kokonaisvaltaista rahoitussuunnittelua, selittävät monimutkaisten mallien tuloksia ja tarjoavat psykologista tukea. Lopputuloksena tutkielma ehdottaa ratkaisuksi hybridimallia, joka yhdistää tekoälyn tehokkuuden inhimilliseen päätöksentekoon ja empatiaan; se on paras lähestymistapa tulevaisuuden salkunhoitoon.
Keywords: machine learning; investment activities; artificial intelligence; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|